Optical, physical and structural properties of zinc-borotellurite glass doped with samarium oxide and samarium oxide nanoparticles - Saleh Abuzlilia, Hajer Saad (2015)
Tellurite glasses are very promising materials for laser and non-linear applications in optics, due to some of their important characteristic features, such as high refractive index, low phonon maxima and low melting point. Addition of small amount of TeO2 into borate glass network enhance glass quality with an improvement in transparency and refractive index. Addition of ZnO into borotellurite glass network produce low rates of crystallization and increase glass forming ability. When other metals oxides are added in tellurite glass system, it can enhance the optical and physical behaviour. It is known that there is only a few reasearch on samarium and samarium nanoparticles doped tellurite glass system. Samarium oxide has high potential for optical applications. Meanwhile,samarium nanoparticles affect the optical properties of the glass system which is due to their smaller size of particles. For this research, two series of zincborotellurite glass: Samarium oxide and Samarium oxide nanoparticles doped zinc-borotellurite glass were successfully synthesized using a conventional meltquenching method. XRD results for both Samarium oxide and Samarium oxide nanoparticles doped zinc-borotellurite glass show that the glasses are in amorphous phase. The physical and optical properties measurements were investigated for both series of zinc-borotellurite glass system. In case of Samarium doped zinc-borotellurite glass system, the density of glass samples was in the range of 3.693-4.285 kg/m3 and was found to be increased with an increasing content of samarium which is due to the formation of nonbridging oxygen. The molar volume of these glasses was in the range of 31.689-30 057 m3 /mol and it was increasesed which is due to the large value of ionic radii and bond length of Sm2O3 compared to TeO2 and increasing in oxygen packing density which results the structure becomes more compact. The non linear trend of refractive index 1.871-2.005 and polarizability 5.716-5.981×10–24cm3 are due to the substitution of ZnO oxides which acts as a modifier and former at certain values of mol %. The FTIR analysis consists of several bands which indicate the characteristic of Te-O and B-O vibrational groups. The optical absorption spectra of these glasses revealed that fundamental absorption edge shifts to longer wavelength as the content of Sm2O3 increases. The decreasing value of the band gap energy from 2.780 eV to 2.528 eV is due to the increasing number of non-bridging oxygen. The value of Urbach energy was in the range 0.689-0.660 eV and it was found to be increased with increasing content of samarium. This is due to the increasing number of TeO4 pyramids as the content of Sm2O3 oxide increases. The presence of TeO4 pyramids results the structure to become less stable. In case of Samarium nanoparticles doped zinc-borotellurite glass system, the density of the prepared glass samples was found in the range 3.644-4.080 kg/m3 and it was to be increased with an increase content of samarium nanoparticles which is due to the low solubility of samarium nanoparticles. The value of molar volume of these glasses was in the range 32.515-31.570 m3/mol and it was found to be decreased with increasing content of samarium nanoparticles because of he dual nature of zinc oxide. The range of refractive index of these glasses are 2.056-2.051 and it was decreased to 0.02 mol% of Sm2O3 NPs which is due to the restriction movement of the electrons with respect to their small size of particles. The increasing trend of refractive index at 5% of samarium nanoparticles is due to the increasing number of non-bridging oxygen. The presence of Sm2O3 nanoparticles was confirmed by using TEM technique with the average size of 22.5 nm. The FTIR spectra revealed the shifting and new absorption peak in the presence of nanoparticles. The absorption edge is found to be shifted to longer wavelength. The decreasing value of the band gap energy from 2.956 eV to 2.980 eV is due to the broadening of the valence band or multivalence structures in the presence of Sm electrons. The value of Urbachenergy is 0.361-0.354 eV and it was found to be increased with increasing concentration of samarium nanoparticles. It is known that materials which possess large value of Urbach energy have higher tendency to convert the weak bonds into defects.